2011
DOI: 10.1111/j.1442-200x.2011.03325.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic, zinc and lactose‐free formula in children with rotavirus diarrhea: Are they effective?

Abstract: A different combination of adjunct therapies did not seem to bring additional value to rehydration therapy in children with rotavirus diarrhea except for in those receiving only zinc and zinc plus S. boulardii. Further studies are required to determine the optimal protocol of adjunct therapy use in children with rotavirus diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 41 publications
2
72
0
4
Order By: Relevance
“…Briefly, only 1 study was adequate for all of the 4 methodological quality assessment parameters 43 and 1 was inadequate for all 4 parameters. 46 Eight studies were rated as adequate 14,16,19,37,43,45,48,51 and 4 were inadequate for generation of the allocation sequence, 17,39,46,47 and the method used for allocation sequence was unclear in 10 studies. 13,18,38,[40][41][42]44,49,50,52 Four studies were adequate, 14,43,45,48 14 studies were unclear, 13,16,18,19,37,38,[40][41][42]44,[49][50][51][52] and 4 studies were inadequate (as they used a method such as alternation.…”
Section: Risk Of Bias Within Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Briefly, only 1 study was adequate for all of the 4 methodological quality assessment parameters 43 and 1 was inadequate for all 4 parameters. 46 Eight studies were rated as adequate 14,16,19,37,43,45,48,51 and 4 were inadequate for generation of the allocation sequence, 17,39,46,47 and the method used for allocation sequence was unclear in 10 studies. 13,18,38,[40][41][42]44,49,50,52 Four studies were adequate, 14,43,45,48 14 studies were unclear, 13,16,18,19,37,38,[40][41][42]44,[49][50][51][52] and 4 studies were inadequate (as they used a method such as alternation.…”
Section: Risk Of Bias Within Included Studiesmentioning
confidence: 99%
“…38,40,42,51 Loss to follow-up was adequate (#10%) in 12 studies 13,16,17,19,[37][38][39][40]43,47,49,50 ; 7 studies were considered inadequate 14,41,[44][45][46]48,52 and 3 studies unclear for loss to followup. 18,47,51 The overall quality was assessed and 4 studies were rated as "good" (low risk for bias), 43,45,48,50 13 studies rated as "fair," which were susceptible to some bias, 13,14,16,18,19,37,38,[40][41][42]44,49,51 and 5 studies rated as "poor" (high risk for bias). 17,39,46,47,52 Findings From Meta-analysis Seventeen studies (2102 participants) reported duration of diarrhea.…”
Section: Risk Of Bias Within Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations